Standardized ileal digestible lysine requirement of white commercial layers in peak egg production (Bioscience Journal, 2017)
This study was conducted to determine the standardized ileal digestible lysine (SID Lys) requirements for white commercial layers in peak egg production phase. A total of two hundred eighty-eight 24 week-old Hy-Line W-36 layers were randomly assigned to one of six treatments groups, with eight replicates of six hens each. A basal diet, SID Lys-deficient, was graded supplemented with L-Lysine HCl (78.4%) in order to produce experimental treatments (6.0, 6.6, 7.2, 7.8, 8.4 and 9.0 g SID Lys/kg diet). Throughout the 16-week-feeding trial (24 to 40 weeks of age) hens had free access to water and mash feed. Data were analyzed as one-way ANOVA and optimum SID Lys level for each dependent variable assessed were estimated using polynomial and linear broken-line regression model. Feed intake and SID Lys intake were both linearly enhanced by graded SID Lys levels. According to linear broken-line regression model, the breakpoint for egg production, egg weight, and egg mass occurred at 8.14, 8.56 and 8.35 g SID Lys/kg diet, respectively. The breakpoint for feed conversion per egg mass (kg/kg) and per dozen of eggs (kg/dozen) occurred at 8.48 and 7.80 g SID Lys/kg diet, respectively. Eggshell weight and albumen weight were unaffected by dietary SID Lys supply. Weight gain and yolk weight reached optimum values at 8.33 and 8.03 g SID Lys/kg diet, respectively, according to linear broken-line regression model. In conclusion, SID Lys requirement for white commercial layers in peak egg production phase is 8.48 g/kg diet, which corresponds to an average daily SID Lys intake of 813 mg/hen.